Effect of the feeding system and the production season on the protein fraction content in milk - Król, Jolanta (Array, 2019)
The objective of the present research was to analyse the protein fraction content in milk, with particular regard to whey proteins, in dependence on the cows’ feeding system (group 1 - extensive, 2 - semi-intensive, 3 - intensive) and production season (spring-summer and autumn-winter). Chemical analysis of the fodder was the base for calculation of energy and protein coverage of nutritional dose. A total of 1,133 milk samples were evaluated (550 in winter and 583 in summer). The milk samples were examined for the somatic cell count (SCC), the basic chemical composition, casein and whey proteins: α-lactalbumin, β-lactoglobulin, bovine serum albumin (BSA), lactoferrin and lysozyme. Higher content of crude protein, including casein, was noticed in milk obtained from cows coming from semi-intensive and intensive farms. However, milk taken from cows fed according to the group 1, which was based on fodder from permanent grasslands, had the highest concentration of major whey proteins - both in the summer (pasture and hay) and winter (hay and haylage) seasons. With the increase of silage and industrial fodder in the feed ration, the content of whey proteins - mainly β-lactoglobulin and lactoferrin - decreased, which was confirmed by the obtained negative correlation coefficients.